Amelioration of Acidic Soil by fly Ash for Trace Elements Up take and Better Crop Yield and Increased Protein Contents in Chick Pea (Cicer arietinum) - Chakrabarty, Ajita; Soni, Preeti; Thetwar, L.K. (Asian Journal of Chemistry, 2010)
The present paper deals with the study of pot experiments on acidic soil of Rehar Basin (major irrigation project) after mixing fly ash in different proportions for better crop yield of chick pea (Cicer arietinum).